2022
DOI: 10.2147/ndt.s390385
|View full text |Cite
|
Sign up to set email alerts
|

Major Depression and Onset of Frontotemporal Dementia

Abstract: Purpose Frontotemporal dementia (FTD) is still a clinical challenge with the highest rate of misdiagnosis and poor outcome. The pathogenetic relationship between depression and neurodegeneration remains unclear. This study evaluated depression prevalence before FTD diagnosis. Patients and Methods The aim was to assess the prevalence and impact of depression on FTD diagnostic process. The clinical characteristics of 72 patients hospitalized in Department of Affective and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…The DMN, primarily active at rest and inactive during cognitive tasks, is associated with introspection, self-referential thinking, and mind-wandering [40, 42]. Our study identified alterations in DMN segregation in both BV-FTD and SV-FTD, highlighting the remarkable dysconnectivity observed in depression, characterized by excessive internal focus [40] Loss of empathy is a common feature in FTD, which shares similarities with depressive symptoms [46]. The FPN is responsible for cognitive control and goal-directed thinking [47].…”
Section: Discussionmentioning
confidence: 88%
“…The DMN, primarily active at rest and inactive during cognitive tasks, is associated with introspection, self-referential thinking, and mind-wandering [40, 42]. Our study identified alterations in DMN segregation in both BV-FTD and SV-FTD, highlighting the remarkable dysconnectivity observed in depression, characterized by excessive internal focus [40] Loss of empathy is a common feature in FTD, which shares similarities with depressive symptoms [46]. The FPN is responsible for cognitive control and goal-directed thinking [47].…”
Section: Discussionmentioning
confidence: 88%